Edible Origami Paper Innovation to Increase Daily Vegetables Intake - Femyta Anindya Putri; Amelia Putri Nuladhani; Rachel Abelyana (Soegijapranata Catholic University, 2025)
Indonesia has a low level of vegetable consumption, especially among children, even though this type of food is essential for growth and health. According to data from the Basic Health Research (Riskesdas), around 30.8% of toddlers in Indonesia experience stunted growth, and about 10.2% suffer from malnutrition. This condition increases the risk of child mortality up to 11.6 times higher compared to children with adequate growth and nutrition. Children tend to dislike vegetables due to their taste, texture, and early habits of consuming fast food. The proposed innovation of edible origami paper serves as a fun, educational, and nutritious approach that is both creative and contextually appropriate, particularly for promoting early nutrition awareness. The innovative formulation in this folding paper utilizes green spinach, purple cabbage, and pumpkin with the addition of a binding agent. Proximate analysis was conducted to determine the main nutritional components, including moisture, ash, protein, fat, carbohydrates, and dietary fiber, and the results were compared with those of fresh vegetables. The analysis showed that the edible origami paper has a higher nutrient density than the fresh materials due to the drying process, which reduces moisture content and increases nutrient concentration. The product also exhibited good physical properties such as high folding strength, allowing it to be folded like conventional origami. This innovation is expected to serve as a creative and contextual approach to enhancing children's nutrition awareness from an early age through an enjoyable, educational, and nutritious medium.